Measurement of Dynamic Response Parameters of an Underdamped System - Singh, Charandeep; Chaparala, Satish; Park, S.B. (Dynamic Behavior of Materials, Volume 1, 2017)
The dynamic behavior of a system is highly influenced by the energy dissipation due to its damping. To clearly understand dynamic behavior, an accurate measurement of damping is very important. One of the most commonly used methods for evaluating damping coefficients is the measurement of decay of free vibrations. The purpose of this study is to introduce a new experimental technique, a pluck test coupled with High speed Digital Image Correlation (DIC) [1] technique, to analyze the dynamic response of underdamped systems. It is further validated comparing the results from this test with those of obtained from the existing techniques such as using laser vibrometer and by using a general purpose single-axis accelerometer. Using the pluck test, an initial displacement is introduced into the system and the response with time is measured using DIC. High speed DIC employs two synchronized high speed digital cameras. Images captured at a high frame rate by high speed cameras are analyzed using 3D DIC software and therefore, a full field dynamic response of the test subject is captured The parameters such as natural frequency and damping ratio are obtained from the measured time history of the displacement using logarithmic decrement method [2]. The test vehicles used in this study to implement this technique are different liquid crystal display (LCD) modules used in commercially available smart phones and Corning® Gorilla® Glass that is used as cover glass in the same.